Electrochemical aptasensor fabricated by anchoring recognition aptamers and immobilizing redox probes on bipolar silica nanochannel array for reagentless detection of carbohydrate antigen 15-3 - Xing, Jun; Han, Qianqian; Liu, Jiyang; Yan, Zhengzheng (Frontiers in Chemistry, 2023)
Timely, convenient, and efficient detection of carbohydrate antigen 15-3 (CA15-3) levels in serum holds significant importance in early screening, diagnostic assistance and prognosis prediction of breast cancer. The development of efficient and convenient electrochemical aptasensors with immobilized redox probes for label-free detection of CA15-3 is highly desirable. In this work, a bipolar silica nanochannel array film (bp-SNA) with two distinct functional domains including nanochannels and an outer surface was employed for the immobilization of recognition ligands and electrochemical redox probes, enabling the construction of a probe-integrated aptasensor for reagentless electrochemical detection of CA15-3. Cost-effective and readily available indium tin oxide (ITO) was used as the supporting electrode for sequential growth of a negatively charged inner layer (n-SNA) followed by a positively charged outer layer (p-SNA). The preparation process of bp-SNA is convenient. Functionalization of amino groups on the outer surface of bp-SNA was modified by aldehyde groups for covalent immobilization of recognition aptamers, further establishing the recognition interface. Within the nanochannels of bp-SNA, the electrochemical redox probe, tri (2,2′-dipyridyl) cobalt (II) (Co(bpy)32+) was immobilized, which experienced a dual effect of electrostatic attraction from n-SNA and electrostatic repulsion from p-SNA, resulting in high stability of the immobilized probes. The constructed aptasensor allowed for reagentless electrochemical detection of CA15-3 ranged from 0.001 U/mL to 500 U/mL with a low detection limit (DL), 0.13 mU/mL). The application of the constructed aptasensor for CA15-3 detection in fetal bovine serum was also validated. This sensor offers advantages of a simple and readily obtainable supporting electrode, easy bp-SNA fabrication, high probe stability and good stability.